Yuval Noah Harari: an critical approach - Arroyo Martínez, Mario (Mercurio Peruano, 2018)
Yuval Noah Harari offers in two recent publications a tight and panoramic vision of human history from the dawn of homo sapiens to the present day, with some at the same time suggestive and disturbing reflections on the future and supposedly probable end of the human species.